[Fishing Boat in Hafnarfjörður] - Streng, Evelyn Fiedler (1975)
Photograph of a fishing boat at Hafnarfjörður. A man in a blue jacket stands in the white, rusted boat below a rope holding fish. A red ship is sat to the right along a wooden dock where cars sit along it. More white ships and buildings are visible in the background.